2005
DOI: 10.1007/s11664-005-0155-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of substrate bias, substrate temperature, and pulse frequency on the microstructures of chromium nitride coatings deposited by pulsed direct current reactive magnetron sputtering

Abstract: Recently, great attention has been devoted to the pulsed direct current (DC) reactive magnetron sputtering technique, due to its ability to reduce arcing and target poisoning, and its capability of producing insulating thin films. In this study, chromium nitride (CrN) coatings were deposited by the bipolar symmetric pulsed DC magnetron reactive sputtering process at different pulse frequency, substrate bias voltage, and the substrate temperature. It was observed that the texture of CrN changed from (111) to (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 31 publications
4
7
0
Order By: Relevance
“…7c. This results in the decreasing of deposition rate as rising of pulsed frequency which is consistent to the conclusion in literature 10,11 .…”
Section: Pulsed Frequencysupporting
confidence: 92%
See 2 more Smart Citations
“…7c. This results in the decreasing of deposition rate as rising of pulsed frequency which is consistent to the conclusion in literature 10,11 .…”
Section: Pulsed Frequencysupporting
confidence: 92%
“…Glocker 4 compared direct current (DC) magnetron and 35 kHz alternating current (AC) magnetron at the same power and reported electron energies, ion densities and deposition rates of 3.2 eV, 6.4 × 10 16 m -3 , 0.70 nm/s for AC, and 2.4 eV, 1.63 × 10 16 m -3 , 0.82 nm/s for DC, respectively. Lee et al 10 reported decreasing deposition rate at pulse frequencies less than 20 kHz, supported by similar results for vanadium oxide sputtering at frequencies up to 350 kHz 11 . Deposition rates were generally found to increase with duty cycles 12,13 .…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…The columnar grain structure is more homogeneous with the higher bias induced condition. This might be due to grain refinement related to the increased surface energy by highly induced bias power [24,27,28].…”
Section: Phase Formation and Microstructurementioning
confidence: 99%
“…As demonstrated in the present study and in e.g., Refs. [17][18][19][20][21], the ion bombardment induced by the substrate bias voltage can greatly affect e.g., the crystallinity, preferential growth direction, stress state and density of deposited thin films and NMLs. Therefore, in this work, Ag[Ge]/AlN NMLs were fabricated with and without RF bias.…”
Section: Introductionmentioning
confidence: 99%